A Novel Modular Device for Biological Impedance Measurements: The Differential Impedimetric Sensor Cell (DISC). Issue 15 (25th April 2018) - Cornelis, Peter; Wackers, Gideon; Thomas, Isabelle; Brand, Max; Putzeys, Tristan; Gennaro, Alessia; Wübbenhorst, Michael; Ingebrandt, Sven; Wagner, Patrick
Abstract : For medical diagnostics, food‐safety analysis, and detection of environmental pollutants, simultaneous detection and quantification of multiple target molecules can be a great advantage. Impedimetric measurements using molecularly imprinted polymers (MIPs), antibodies or aptamers as biomimetic sensors are becoming a well‐established technique for detecting, quantifying, and analyzing various biological targets such as DNA, proteins, and small molecules. The most commonly implemented systems use non‐Faradaic impedance spectroscopy. Adding a redox probe such as silver/silver chloride allows for the use of Faradaic impedance spectroscopy techniques using redox‐active molecules such as ferricyanide thereby extending the range of possible applications. Furthermore, the ability to perform differential measurements allows for the use of undiluted patient samples which significantly simplifies sample preparation. Therefore, adapting this low‐cost technique to simultaneously perform differential measurements on multiple targets and making it easy to use has great potential in a wide range of applications. In this work, a system that meets these requirements is successfully designed and fabricated. Up to eight different targets can be quasi‐simultaneously analyzed. Furthermore, the system is validated against a high‐resolution dielectric spectrometer (Novocontrol, Alpha analyzer) using well‐characterized samples at different temperatures over the whole frequency range (10 Hz–100 kHz). Abstract : In medical diagnostics, food‐safety analysis, and detection of environmental pollutants, simultaneous detection and quantification of multiple target molecules can be invaluable. Furthermore, the ability to perform differential measurements enables analysis of undiluted patient samples, which significantly simplifies sample preparation. In this work, a successful prototype system based on impedance spectroscopy that meets these requirements is presented and validated.